The effect of NaOH concentration on silica leaching process from rice husk ash in South Sulawesi Province, Indonesia - Rahim, Herlina; Prameswara, Gyan; Gusmadi, Muh. Irfan Wijaya; Jamaluddin, Jamaluddin (Jurnal Rekayasa Proses, 2024)
The issue of waste and raw material sources has become common in the processing industry. The ideal solution is to use waste as a substitute for primary material. The processing of rice husk waste for silica extraction can aid in resolving the issue of solid waste accumulation in the agricultural industry. The extraction process begins with burning and ashing the husk waste to increase the silica content. At 750 oC, the silica content increased to 88.06%. The leaching process was carried out to dissolve Si, and observe the behavior of other major elements, such as K, Ca, and P, from rice husk ash. Leaching was carried out in a 3-neck flask with external heating. The effect of the concentration of NaOH solution on elements recovery was studied in this experiment. The highest recovery of Si, K, Ca, and P reached 89.94%, 89.04%, 61.37%, and 78.61%, respectively, at 3 N NaOH concentration, 120 minutes, 300 rpm, and 10% S/L ratio. There was also a precipitate of Na3PO4 formed in the product solution after being left for 24 hours. This provides insight into the decantation process before precipitation using Al(OH)3 in zeolite production.